On be...ing political: Empat model identitas ramah-gereja di bawah bayang-bayang kanopi suci kebangsaan - Adiprasetya, Joas (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
This article discusses the idea of a hospitable church that struggles under the sacred canopy of the state, especially in the Indonesian context. By using Stanley Hauerwas’ social ethics and ecclesiology that views the church as an exemplary community, this article proposes an ecclesial model that maintains the tension of being true to its nature on the one hand and being political on the other hand. Such a model is demonstrated through its four dimensions: beholding, becoming, belonging, and befriending. The paper ends with a conclusion, in which the author reflects on the four dimensions by using the perspective of the four classical marks of the church (notae ecclesiae). AbstrakArtikel ini membahas gagasan mengenai gereja dengan identitas-ramah yang berjuang di bawah kanopi suci negara, khususnya dalam konteks Indonesia. Dengan menggunakan etika sosial dan eklesiologi Stanley Hauerwas, yang memandang gereja sebagai komunitas eksemplaris, artikel ini mengusul-kan model gerejawi yang mempertahankan ketegangan antara menjadi setia pada hakikatnya di satu sisi dan menjadi politis di sisi lain. Model semacam itu ditunjukkan melalui empat dimensinya: beholding, becoming, belonging, dan befriending. Makalah diakhiri dengan kesimpulan yang di dalamnya penulis merefleksikan empat dimensi di atas dengan menggunakan perspektif empat tanda klasik gereja (notae ecclesiae).